Artisanal gastronomy and local tourism: the meaning of Cassoleta Cheese, Castellón (Spain) - Fusté Forné, Francesc (2018)
Local products are one of the most outstanding indicators of identity, conveying the cultural, natural and rural authenticity of a destination. This sense of place is communicated to visitors and tourists through the narratives of local actors – for example, the sellers of local produce. This investigation is intended to analyze the meanings that these agents attach to Cassoleta cheese, a local artisanal food produced in the Spanish region of Valencia. The methodology used was based on five semi-structured interviews with local sellers conducted in the city of Castellón, the capital of the province, where there is a long tradition of producing this cheese. Results of this research offer insights into the narratives linked to Cassoleta cheese, which are predominantly based on its historical connection to the territory, its daily consumption by local inhabitants thanks to its versatility in the kitchen, and its appeal to tourists who seek artisanal products. This article provides a series of theoretical and practical implications; on the one hand, theoretical analysis may serve to broaden the field of study of culinary tourism and its relation to gastronomy as an element of cultural and rural identity. On the other hand, understanding local produce from the perspective of actors in the region can help promote a destination based on their authentic narratives.